Cotton fabric with fireproof and heat-insulating functions as well as preparation method and application of cotton fabric
The treatment of cotton fabrics by immersion and chemical vapor deposition methods solves the problems of complex and long cycles of cotton fabric preparation in the prior art, and achieves the rapid preparation of cotton fabrics with good thermal insulation and fire-retardant flame retardant type.
Patent Information
- Application Number
- CN202411900825.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The existing cotton fabrics with fire-resistant and thermal insulation properties are complex in production processes, with a long cycle, and cannot be produced and prepared quickly.
After heating the cotton fabric by soaking it in a silane coupling agent solution, rinsing it with anhydrous ethanol and drying it, followed by depositing silica fibers on the surface of the cotton fabric by chemical vapor deposition.
This method simplifies the preparation process, shortens the production cycle, improves the deposition efficiency of silica fibers, and makes cotton fabrics have good thermal insulation and fire-retardant flame retardant.
Smart Images

Figure CN119736785A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a cotton fabric with fireproof and heat-insulating functions and a preparation method and application thereof, belonging to the technical field of fireproof and heat-insulating composite materials and preparation thereof. Background Art
[0002] There are a lot of flammable materials in the interior of high-rise buildings, such as curtains, sheets and other cotton fabrics. Once a fire occurs, cotton fabrics will produce a lot of smoke during the combustion process, which contains toxic substances, and inhalation will be harmful to human health. At the same time, cotton fabrics are flammable and burn quickly, causing the fire to spread rapidly, making it difficult for people to escape and rescue tasks, and causing casualties and property losses. Traditional modification methods for cotton fabrics with fireproof and heat-insulating properties, such as coating, padding and baking, and immersion and drying, have complex production processes and long production cycles, and cannot be quickly produced and prepared.
[0003] Therefore, there is an urgent need for a cotton fabric with fireproof and heat-insulating functions that can be quickly prepared and can be used in the event of a fire, and a preparation method thereof. Summary of the invention
[0004] Aiming at the problems that the existing cotton fabric with fireproof and heat-insulating properties has a complicated production process, a long production cycle and cannot be produced and prepared quickly, the present invention provides a cotton fabric with fireproof and heat-insulating functions and a preparation method and application thereof.
[0005] The technical solution of the present invention:
[0006] One of the purposes of the present invention is to provide a method for preparing a cotton fabric having fireproof and heat-insulating functions, the method comprising the following steps:
[0007] (1) soaking cotton fabric in a silane coupling agent solution, taking out the cotton fabric after heating, rinsing with anhydrous ethanol and drying to obtain a pretreated cotton fabric;
[0008] (2) Silica fibers are deposited on the surface of pretreated cotton fabric by chemical vapor deposition, and then taken out and dried to obtain cotton fabric with fireproof and heat-insulating functions.
[0009] It is further defined that the silane coupling agent solution in (1) is prepared by mixing KH550, deionized water and anhydrous ethanol in a mass ratio of 0.5:1:10.
[0010] It is further defined that the heating treatment temperature in (1) is 90° C. and the time is 5 to 60 minutes.
[0011] It is further defined that the drying temperature in (1) is 100° C. and the drying time is 60 min.
[0012] It is further defined that the process of depositing silica fibers by chemical vapor deposition in (2) is as follows: methyl-trimethoxysilane and ammonia water are placed in two containers respectively, and placed together with the pretreated cotton fabric in a vacuum dryer, which is then sealed and evacuated and then placed in a constant temperature box for heating.
[0013] It is further defined that the volume ratio of methyl-trimethoxysilane and aqueous ammonia is 1:1.
[0014] It is further specified that the container is sealed and evacuated to a vacuum degree of -0.094 to -0.092 MPa, and placed in a constant temperature box at 100°C for 7 hours.
[0015] It is further defined that the drying temperature in (2) is 50°C and the drying time is 1.5 h.
[0016] The second object of the present invention is to provide a cotton fabric with fireproof and heat-insulating functions prepared by the above method.
[0017] The third object of the present invention is to provide an application of the above-mentioned cotton fabric with fireproof and heat-insulating functions, specifically for making fire blankets and heat-insulating blankets.
[0018] Beneficial effects:
[0019] The present invention deposits silica fibers on the surface of cotton fabric, so that the cotton fabric has the characteristics of low thermal conductivity and good thermal insulation. After the silica nanofibers are deposited on the surface of the cotton fabric, a silica protective layer will be formed when heated, thereby isolating external heat and oxygen, showing good fire retardancy. Compared with the prior art, the present invention has at least the following advantages:
[0020] (1) Before depositing silica fibers on the surface of the cotton fabric of the present invention, the cotton fabric is pretreated with a silane coupling agent, which effectively improves the deposition efficiency of the silica fibers and effectively shortens the preparation cycle of the cotton fabric with fireproof and heat-insulating functions.
[0021] (2) The present invention uses chemical vapor deposition to deposit silica fibers on the surface of cotton fabrics, which can be successfully prepared under a low temperature environment of 100°C. The materials used are cheap and easy to obtain, and the equipment is simple, which is suitable for promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a real picture of cotton fabric;
[0023] Figure 2 This is the SEM photo of cotton fabric;
[0024] Figure 3 This is a physical picture of the cotton fabric after pretreatment in Example 1;
[0025] Figure 4is a SEM photo of the cotton fabric after pretreatment in Example 1;
[0026] Figure 5 This is a physical picture of the cotton fabric with fireproof and heat-insulating functions prepared in Example 1;
[0027] Figure 6 This is a SEM photo of the cotton fabric with fireproof and heat-insulating functions prepared in Example 1;
[0028] Figure 7 It is a comparison chart of the mass growth rate of cotton fabrics in the chemical vapor deposition process of Examples 1 to 3 and Comparative Examples 1 to 3;
[0029] Figure 8 This is a graph showing the thermal insulation performance test results of the cotton fabric with fireproof and thermal insulation functions prepared in Example 1;
[0030] Fig. 9 This is the flame retardant test result of cotton fabric;
[0031] Fig.10 This is a flame retardant test result diagram of the cotton fabric with fireproof and heat-insulating functions prepared in Example 1;
[0032] Fig.11 This is a comparison chart of infrared spectra of the cotton fabric in Example 1, the pretreated cotton fabric, and the cotton fabric with fireproof and heat-insulating functions. DETAILED DESCRIPTION
[0033] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0034] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0035] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0036] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art, and the purity of the solid and liquid reagents used is analytically pure.
[0037] Example 1
[0038] (1) Prepare silane coupling agent solution:
[0039] Weigh KH550 silane coupling agent, deionized water and anhydrous ethanol in a mass ratio of 0.5:1:10. Specifically, weigh 5g, 10g and 100g respectively and put them in a beaker.
[0040] (2) Prepare the reaction matrix:
[0041] Soak the cotton fabric in the silane coupling agent solution, heat it to 90°C, keep it warm for 10 minutes, take it out, rinse it in anhydrous ethanol, and dry it in an oven at 100°C for later use.
[0042] (3) Preparation of raw materials for synthesis of silica nanofibers:
[0043] Use 98% pure methyl-trimethoxysilane as reactant and 25% mass concentration ammonia water as catalyst in a volume ratio of 1:1. Specifically, measure 1.5 ml of each and place them in two small beakers respectively.
[0044] (4) Deposition of silica nanofibers:
[0045] Place a small beaker containing reactants and catalysts at the bottom of the vacuum dryer, place the dried reaction substrate on the reaction rack in the vacuum dryer, seal the vacuum dryer and evacuate it to a vacuum degree of -0.092 MPa, and then place the vacuum dryer in a constant temperature box at 100°C for 7 hours.
[0046] (5) The vacuum dryer is taken out from the thermostatic box, and after cooling to room temperature, the vacuum dryer is opened, and the reaction substrate with silica nanofibers deposited on the surface is taken out from the vacuum dryer, and then placed in a thermostatic box for drying at a temperature of 50°C for 1.5 hours. After drying, the substrate is taken out after cooling, thereby obtaining a cotton fabric with fireproof and heat-insulating functions.
[0047] Example 2
[0048] (1) Prepare silane coupling agent solution:
[0049] Weigh KH550 silane coupling agent, deionized water and anhydrous ethanol in a mass ratio of 0.5:1:10. Specifically, weigh 5g, 10g and 100g respectively and put them in a beaker.
[0050] (2) Prepare the reaction matrix:
[0051] Soak the cotton fabric in the silane coupling agent solution, heat it to 90°C, keep it warm for 20 minutes, take it out, rinse it in anhydrous ethanol, and dry it in a 100°C oven for later use.
[0052] (3) Preparation of raw materials for synthesis of silica nanofibers:
[0053] Use 98% pure methyl-trimethoxysilane as reactant and 25% mass concentration ammonia water as catalyst in a volume ratio of 1:1. Specifically, measure 1.5 ml each and place it in two small beakers.
[0054] (4) Deposition of silica nanofibers:
[0055] Place a small beaker containing reactants and catalysts at the bottom of the vacuum dryer, place the dried reaction substrate on the reaction rack in the vacuum dryer, seal the vacuum dryer and evacuate it to a vacuum degree of -0.092 MPa, and then place the vacuum dryer in a constant temperature box at 100°C for 7 hours.
[0056] (5) The vacuum dryer is taken out from the thermostatic box, and after cooling to room temperature, the vacuum dryer is opened, and the reaction substrate with silica nanofibers deposited on the surface is taken out from the vacuum dryer, and then placed in a thermostatic box for drying at a temperature of 50°C for 1.5 hours. After drying, the substrate is taken out after cooling, thereby obtaining a cotton fabric with fireproof and heat-insulating functions.
[0057] Example 3
[0058] (1) Prepare silane coupling agent solution:
[0059] Weigh KH550 silane coupling agent, deionized water and anhydrous ethanol in a mass ratio of 0.5:1:10. Specifically, weigh 5g, 10g and 100g respectively and put them in a beaker.
[0060] (2) Prepare the reaction matrix:
[0061] Soak the cotton fabric in the silane coupling agent solution, heat it to 90°C, keep it warm for 30 minutes, take it out, rinse it in anhydrous ethanol, and dry it in a 100°C oven for later use.
[0062] (3) Preparation of raw materials for synthesis of silica nanofibers:
[0063] Use 98% pure methyl-trimethoxysilane as reactant and 25% mass concentration ammonia water as catalyst in a volume ratio of 1:1. Specifically, measure 1.5 ml each and place it in two small beakers.
[0064] (4) Deposition of silica nanofibers:
[0065] Place a small beaker containing reactants and catalysts at the bottom of the vacuum dryer, place the dried reaction substrate on the reaction rack in the vacuum dryer, seal the vacuum dryer and evacuate it to a vacuum degree of -0.094 MPa, and then place the vacuum dryer in a constant temperature box at 100°C for 7 hours.
[0066] (5) The vacuum dryer is taken out from the thermostatic box, and after cooling to room temperature, the vacuum dryer is opened, and the reaction substrate with silica nanofibers deposited on the surface is taken out from the vacuum dryer, and then placed in a thermostatic box for drying at a temperature of 50°C for 1.5 hours. After drying, the substrate is taken out after cooling, thereby obtaining a cotton fabric with fireproof and heat-insulating functions.
[0067] Comparative Example 1
[0068] (1) Prepare the reaction matrix:
[0069] Cotton fabric was used as a reaction substrate, washed with deionized water for 30 min, and then placed in a 100°C oven for drying.
[0070] (2) Preparation of raw materials for synthesis of silica nanofibers:
[0071] Use 98% pure methyl-trimethoxysilane as reactant and 25% mass concentration ammonia water as catalyst in a volume ratio of 1:1. Specifically, measure 1.5 ml each and place it in two small beakers.
[0072] (3) Deposition of silica nanofibers:
[0073] Place a small beaker containing reactants and catalysts at the bottom of the vacuum dryer, place the dried cotton fabric on the reaction rack in the vacuum dryer, seal the vacuum dryer and evacuate it to a vacuum degree of -0.093 MPa, and then place the vacuum dryer in a constant temperature box at 100°C for 7 hours.
[0074] (4) The vacuum dryer is taken out from the thermostatic box, and after cooling to room temperature, the vacuum dryer is opened, and the cotton fabric with silica nanofibers deposited on the surface is taken out from the vacuum dryer, and then placed in a thermostatic box for drying at a temperature of 50°C and a drying time of 1.5 hours. After drying, the cotton fabric is taken out after cooling, thereby obtaining a cotton fabric with fireproof and heat-insulating functions.
[0075] Comparative Example 2
[0076] (1) Prepare silane coupling agent solution:
[0077] Weigh KH550 silane coupling agent, deionized water and anhydrous ethanol in a mass ratio of 0.5:1:10. Specifically, weigh 5g, 10g and 100g respectively and put them in a beaker.
[0078] (2) Prepare the reaction matrix:
[0079] Soak the cotton fabric in the silane coupling agent solution, heat it to 90°C, keep it warm for 5 minutes, take it out, rinse it in anhydrous ethanol, and dry it in a 100°C oven for later use.
[0080] (3) Preparation of raw materials for synthesis of silica nanofibers:
[0081] Use 98% pure methyl-trimethoxysilane as reactant and 25% mass concentration ammonia water as catalyst in a volume ratio of 1:1. Specifically, measure 1.5 ml each and place it in two small beakers.
[0082] (4) Deposition of silica nanofibers:
[0083] Place a small beaker containing reactants and catalysts at the bottom of the vacuum dryer, place the dried reaction substrate on the reaction rack in the vacuum dryer, seal the vacuum dryer and evacuate it to a vacuum degree of -0.092 MPa, and then place the vacuum dryer in a constant temperature box at 100°C for 7 hours.
[0084] (5) The vacuum dryer is taken out from the thermostatic box, and after cooling to room temperature, the vacuum dryer is opened, and the reaction substrate with silica nanofibers deposited on the surface is taken out from the vacuum dryer, and then placed in a thermostatic box for drying at a temperature of 50°C for 1.5 hours. After drying, the substrate is taken out after cooling, thereby obtaining a cotton fabric with fireproof and heat-insulating functions.
[0085] Comparative Example 3
[0086] (1) Prepare silane coupling agent solution:
[0087] Weigh KH550 silane coupling agent, deionized water and anhydrous ethanol in a mass ratio of 0.5:1:10. Specifically, weigh 5g, 10g and 100g respectively and put them in a beaker.
[0088] (2) Prepare the reaction matrix:
[0089] Soak the cotton fabric in the silane coupling agent solution, heat it to 90°C, keep it warm for 60 minutes, take it out, rinse it in anhydrous ethanol, and dry it in a 100°C oven for later use.
[0090] (3) Preparation of raw materials for synthesis of silica nanofibers:
[0091] Use 98% pure methyl-trimethoxysilane as reactant and 25% mass concentration ammonia water as catalyst in a volume ratio of 1:1. Specifically, measure 1.5 ml each and place it in two small beakers.
[0092] (4) Deposition of silica nanofibers:
[0093] Place a small beaker containing reactants and catalysts at the bottom of the vacuum dryer, place the dried reaction substrate on the reaction rack in the vacuum dryer, seal the vacuum dryer and evacuate it to a vacuum degree of -0.092 MPa, and then place the vacuum dryer in a constant temperature box at 100°C for 7 hours.
[0094] (5) The vacuum dryer is taken out from the thermostatic box, and after cooling to room temperature, the vacuum dryer is opened, and the reaction substrate with silica nanofibers deposited on the surface is taken out from the vacuum dryer, and then placed in a thermostatic box for drying at a temperature of 50°C for 1.5 hours. After drying, the substrate is taken out after cooling, thereby obtaining a cotton fabric with fireproof and heat-insulating functions.
[0095] Comparative Example 4
[0096] (1) Prepare silane coupling agent solution:
[0097] Weigh KH550 silane coupling agent, deionized water and anhydrous ethanol in a mass ratio of 0.5:1:10. Specifically, weigh 5g, 10g and 100g respectively and put them in a beaker.
[0098] (2) Prepare the reaction matrix:
[0099] Soak the cotton fabric in the silane coupling agent solution, heat it to 90°C, keep it warm for 10 minutes, take it out, rinse it in anhydrous ethanol, and dry it in a 100°C oven for later use.
[0100] (3) Preparation of raw materials for synthesis of silica nanofibers:
[0101] Take methyl-trimethoxysilane with a purity of 98% as a reactant and measure 1.5 ml into a small beaker.
[0102] (4) Deposition of silica nanofibers:
[0103] Place a small beaker containing the reactants at the bottom of the vacuum dryer, place the dried reaction substrate on the reaction rack in the vacuum dryer, seal the vacuum dryer and evacuate it to a vacuum degree of -0.093 MPa, and then place the vacuum dryer in a constant temperature box at 100°C for 7 hours.
[0104] (5) The vacuum dryer is taken out from the thermostat, and after cooling to room temperature, the vacuum dryer is opened, and the reaction substrate is taken out from the vacuum dryer, and then placed in a thermostat for drying at a temperature of 50°C for 1.5 hours. After drying, the substrate is taken out after cooling.
[0105] Comparative Example 5
[0106] (1) Prepare silane coupling agent solution:
[0107] Weigh KH550 silane coupling agent, deionized water and anhydrous ethanol in a mass ratio of 0.5:1:10. Specifically, weigh 5g, 10g and 100g respectively and put them in a beaker.
[0108] (2) Prepare the reaction matrix:
[0109] Soak the cotton fabric in the silane coupling agent solution, heat it to 90°C, keep it warm for 10 minutes, take it out, rinse it in anhydrous ethanol, and dry it in a 100°C oven for later use.
[0110] (3) Preparation of raw materials for synthesis of silicon carbide nanofibers:
[0111] Use 99% pure trimethylchlorosilane as the reactant and 25% mass concentration ammonia water as the catalyst in a volume ratio of 1:1. Specifically, measure 1.5 ml each and place it in two small beakers.
[0112] (4) Deposition of silicon carbide nanofibers:
[0113] Place a small beaker containing reactants and catalysts at the bottom of the vacuum dryer, place the dried reaction substrate on the reaction rack in the vacuum dryer, seal the vacuum dryer and evacuate it to a vacuum degree of -0.093 MPa, and then place the vacuum dryer in a constant temperature box at 100°C for 7 hours.
[0114] (5) The vacuum dryer is taken out from the thermostat, and after cooling to room temperature, the vacuum dryer is opened, and the reaction substrate with silicon carbide nanofibers deposited on the surface is taken out from the vacuum dryer, and then placed in a thermostat for drying at a temperature of 50°C for 1.5 hours. After drying, the substrate is taken out after cooling.
[0115] Effect example
[0116] (1) The mechanical properties, mass growth rate (mass change of the reaction substrate before and after chemical vapor deposition), thermal insulation properties and flame retardant properties of the cotton fabric raw material, Examples 1 to 3 and Comparative Examples 1 to 5 were characterized. The results are shown in Tables 1 and Figure 7 As shown:
[0117] Table 1
[0118]
[0119] Among them, the mechanical properties test refers to the tensile test of GB / T 3923.1-2013. The "—" in the table means that this cotton fabric does not meet the requirements and no further performance test is carried out or relevant tests cannot be carried out.
[0120] As shown in Table 1, compared with Example 1, since the cotton fabric in Comparative Example 1 was not treated in the silane coupling agent solution, the content of silica nanofibers on its surface after chemical vapor deposition was lower than that in Example 1, which shows that the cotton fabric pretreated with KH550 silane coupling agent is conducive to subsequent chemical vapor deposition. Compared with Example 3, since Comparative Example 2 was treated in the silane coupling agent solution for too long, the fiber surface contained a large amount of silane coupling agent macromolecules, which reduced the porosity of the cotton fabric fiber, and the content of silica nanofibers on its surface after chemical vapor deposition was lower than that in Example 3. Compared with Example 1, Comparative Example 4 did not react due to the lack of catalytic effect of ammonia water, and the mass change before and after chemical vapor deposition was very small. Compared with Example 1, Comparative Example 5 replaced the reactant with trimethylchlorosilane, and the other reaction conditions were the same, and no reaction occurred, and the mass change before and after chemical vapor deposition was very small.
[0121] (2) The macroscopic and microscopic morphologies of the cotton fabric in Example 1, the pretreated cotton fabric, and the cotton fabric with fireproof and heat-insulating functions were characterized. The results are as follows: Figures 1 to 6 As shown by Figure 1 It can be seen that the cotton fabric in Example 1 has a smooth surface; Figure 2 It can be seen that the surface of the cotton fabric fiber in Example 1 is smooth; Figure 3 It can be seen that the surface of cotton fabric after pretreatment is rough; Figure 4 It can be seen that the surface of cotton fabric fibers after pretreatment is rough and contains a large number of silane coupling agent macromolecules; Figure 5 It can be seen that the cotton fabric with fireproof and heat-insulating functions has a rough surface and obvious white fibers; Figure 6 It can be seen that the cotton fabric fiber surface with fireproof and heat-insulating functions is rough, and a large amount of silica nanofibers are deposited on the fibers.
[0122] (3) The thermal insulation performance of the cotton fabric with fireproof and heat-insulating functions prepared in Example 1 was tested. The specific testing method was as follows: the cotton fabric with fireproof and heat-insulating functions prepared in Example 1 was placed on a heating plate at 200° C. and infrared imaging was performed. The results were as follows: Figure 8 As shown by Figure 8 It can be seen that cotton fabrics with fireproof and heat-insulating functions can protect fingers from burns.
[0123] (4) The flame retardant properties of the cotton fabric raw material and the cotton fabric with fireproof and heat-insulating functions prepared in Example 1 were tested. The results were as follows: Fig. 9 and Fig.10 As shown by Fig. 9 and Fig.10 It can be seen that Fig. 9 It can be seen that the cotton fabric raw material is placed between the chocolate bear and the butane flame for fire retardancy test. The test time is 60s. At the 5th second, the butane flame burns through the cotton fabric. Until 60s, the chocolate bear is still burning by the flame. When the burning ends, there is obvious carbonization on the surface of the chocolate bear. Fig.10 It can be seen that the cotton fabric with fireproof and heat-insulating functions prepared in Example 1 was placed between a chocolate bear and a butane flame for a fire retardant test. The test time was 60 seconds. Until the end of the combustion, the flame still did not burn through the cotton fabric with fireproof and heat-insulating functions prepared in Example 1, and the surface of the chocolate bear was not carbonized.
[0124] (5) The infrared spectra comparison of the cotton fabric in Example 1, the pretreated cotton fabric and the cotton fabric with fireproof and heat-insulating functions are shown in FIG. Fig.11 As shown by Fig.11 It can be seen that 1276cm -1 The absorption peak at 781 cm is the antisymmetric stretching vibration peak of Si-O-Si. -1 The absorption peak at 840 cm is Si-C. -1 、443cm -1 The absorption peaks at 1430 cm-1 are the symmetrical stretching vibration and bending vibration of Si-O-Si. -1 The peak appearing at is the characteristic absorption peak of the NH internal deformation vibration of the -NH2 functional group. The surface of the cotton fabric treated with the silane coupling agent solution contains more hydroxyl groups, which makes it easier to deposit silica nanofibers during the chemical vapor deposition process.
[0125] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing a cotton fabric with fireproof and heat-insulating functions, characterized in that: include: (1) soaking cotton fabric in a silane coupling agent solution, taking out the cotton fabric after heating, rinsing with anhydrous ethanol and drying to obtain a pretreated cotton fabric; (2) Silica fibers are deposited on the surface of pretreated cotton fabric by chemical vapor deposition, and then taken out and dried to obtain cotton fabric with fireproof and heat-insulating functions.
2. The preparation method according to claim 1, characterized in that: (1) The silane coupling agent solution is prepared by mixing KH550, deionized water and anhydrous ethanol in a mass ratio of 0.5:1:
10.
3. The preparation method according to claim 1, characterized in that: (1) The heating treatment temperature is 90°C and the time is 5 to 60 minutes.
4. The preparation method according to claim 1, characterized in that: (1) The drying temperature is 100°C and the drying time is 60 min.
5. The preparation method according to claim 1, characterized in that: (2) The process of depositing silica fiber by chemical vapor deposition is as follows: methyl-trimethoxysilane and ammonia water are placed in two containers respectively, and the two containers are placed together with the pretreated cotton fabric in a vacuum dryer, which is then sealed and evacuated and then placed in a constant temperature box for heating.
6. The preparation method according to claim 5, characterized in that: The volume ratio of methyl-trimethoxysilane and ammonia water is 1:
1.
7. The preparation method according to claim 5, characterized in that: Seal and evacuate to a vacuum degree of -0.094 to -0.092 MPa, and place in a constant temperature box at 100°C for 7 hours.
8. The preparation method according to claim 1, characterized in that: (2) The drying temperature is 50°C and the drying time is 1.5 hours.
9. A cotton fabric with fireproof and heat-insulating functions prepared by the method according to any one of claims 1 to 8.
10. An application of the cotton fabric with fireproof and heat-insulating functions according to claim 9, characterized in that: Used to make fire blankets and thermal insulation blankets.
Citation Information
Patent Citations
Self-extinguishing flame-retardant cotton fabric and preparation method and application thereof
CN109944070A
Carbon fiber / nanometer silicon dioxide compound as well as preparation method and application thereof
CN112210397A
Heat insulation fireproof structure and manufacturing method thereof
CN117627194A
Gas barrier laminated film for vacuum heat insulating material, and vacuum heat insulating material
JP2010284855A